2016
DOI: 10.1097/pts.0000000000000325
|View full text |Cite
|
Sign up to set email alerts
|

Improving Incident Reporting Among Physician Trainees

Abstract: Background Preventable medical harm is a leading cause of death in the United States. Incident reporting systems have been identified as the primary method to capture medical error and harm. Incident underreporting remains common, particularly among physician trainees. Methods We conducted a single-center, quasi-experimental study to examine how incident reporting education and weekly Patient Safety Rounds would affect incident reporting among trainees. Results Over 6 months, 73 resident physicians partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 11 publications
0
20
0
2
Order By: Relevance
“…For many institutions, particularly large institutions with multiple participating sites, it is not practical to implement and sustain all these strategies. Articles highlighting sustained improvements 6,11,18 used a combination of behavior modeling, coupled with surveys and messaging, and required limited financial support, but some time and dedication by leaders and educators. The survey creates awareness, the behavior modeling is critical for educational purposes, and the reminders help to reinforce the new behavior and embed it into routine patient care activities.…”
Section: Discussionmentioning
confidence: 99%
“…For many institutions, particularly large institutions with multiple participating sites, it is not practical to implement and sustain all these strategies. Articles highlighting sustained improvements 6,11,18 used a combination of behavior modeling, coupled with surveys and messaging, and required limited financial support, but some time and dedication by leaders and educators. The survey creates awareness, the behavior modeling is critical for educational purposes, and the reminders help to reinforce the new behavior and embed it into routine patient care activities.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study (27), the results of qualitative analysis of the residents' interviews after patient safety education showed that they mentioned that they had found it quite difficult to carry out the course content in practice, the information learned faded away after the course, and it would be helpful to organize refresher courses. In addition, barriers related to behavioral control like high work-pressure might be effective (28).…”
Section: Discussionmentioning
confidence: 94%
“…However, the incident reporting rate decreased from 34 per 100 admissions in the first month after the intervention to 16% in the sixth month in the follow-up phase. In a study (27) in the US, where 63 participants were included in an education program for IRS implementation, the numbers of events reported over the period of six months were 10 in the first month, 6 in the second month, 10 in the third month, 18 in the fourth month, 11 in the fifth month, and 6 in the sixth month. Which in total might be less than in the current study but given the different sites of the studies, as it wasn't in a PICU with all its complex health care disciplines, but was on a whole hospital, with its various departments, whether critical care or not.…”
Section: Discussionmentioning
confidence: 99%
“…Describing what could have happened and making suggestions to prevent similar events allowed students to take ownership for improving the healthcare system. This will prepare students for their roles as interns and residents ready to contribute to a culture of safety as mandated by the Accreditation Council for Graduate Medical Education and underscored in the Clinical Learning Environment Review Pathways to Excellence 14 15 37…”
Section: Discussionmentioning
confidence: 99%
“…Reporting can potentially be increased through patient safety education, culture change,12 13 highlighting the importance of medical error reporting,14 15 and teaching how to file incident reports. There is scant literature on what kinds of errors students see during clinical rotations and their reporting behaviours 9 10.…”
Section: Introductionmentioning
confidence: 99%